Investigation of ill-defined causes of death: assessment of a program's performance in a State from the Northeastern region of Brazil - Elisabeth Barboza França; Carolina Cândida da Cunha; Ana Maria Nogales Vasconcelos; Juan José Cortez Escalante; Daisy Xavier de Abreu; Raquel Barbosa de Lima; Otaliba Libânio de Morais Neto (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: The proportion of ill-defined causes of death (IDCD) was persistently high in some regions of Brazil in 2004. In 2005, the Brazilian government implemented a project in order to decrease this proportion, especially in higher priority states and municipalities. This study aimed to evaluate the performance of this project in Alagoas - a state from the Northeast region of Brazil. METHOD: We selected a probabilistic sample of 18 municipalities. For all IDCD identified in 2010, we collected the verbal autopsy (VA) questionnaires used for home investigation, and the Ministry of Health (MoH) form, which contains information about the final disease and cause of death taken from hospital records, autopsies, family health teams, and civil registry office records. The completion rate of the MoH form and VA was calculated using the number of deaths with specific causes assigned among investigated deaths. RESULTS: A total of 681 IDCD were recorded in 2010 in the sample, of which 26% had a MoH and/or VA3 forms completed. Although the majority of cases were attended by health professionals during the terminal disease, the completion rate was 45% using the MoH form and 80% when VA was performed. CONCLUSIONS: Our findings provide evidence that the training of the epidemiological surveillance teams in the investigation and certification of causes of death could contribute to improve the quality of mortality data.